THE ROLE OF THE EDUCATION SYSTEM IN POVERTY REDUCTION - Ne’matjonov Asadbek; Egamberdiyev Shavkatbek (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article analyzes the important role of the educational system in poverty reduction. The impact of education on economic and social empowerment, skill development, vocational education, and the importance of innovative education programs in combating poverty are examined. At the same time, issues of the quality of education, its equal access and integration with public policy are discussed. The article provides strategic recommendations for states and organizations, showing practical ways to reduce poverty through the development of an educational system. This work highlights the contribution of education to the sustainable development of society.